Business liability and economic damages - Gilbert, Scott D. (Economics collection., 2016)
Businesses exist to provide goods and services to customers, and in doing so they take risks. Among these risks is the chance of losing money in lawsuits filed by customers, employees, and others negatively impacted by the business. Insurance provides some protection against these liabilities, but lawsuits still take their toll. This book covers the subject of economic damages and its role in insurance claims and lawsuits against businesses. After reading and understanding this book, the reader will be able to identify economic damages as a component of business liability, describe the business risk posed by economic damages, explain the key determinants of economic damages, and estimate economic damages and business loss in a variety of cases.